2008
DOI: 10.1002/btpr.22
|View full text |Cite
|
Sign up to set email alerts
|

Novel methods for storage stability and release of Bacillus spores

Abstract: Bacillus subtilis spores were immobilized in activated charcoal and tapioca and filled with acacia gum. These formulations were tested for spore stability during storage at temperatures ranging from 408C to 908C and for bacterial release. Thermodynamic analysis showed that immobilization of spores in acacia gum significantly increased their viability compared with unprotected spores. The viability was further increased when suspensions of spores in acacia gum were added to granules of charcoal and tapioca. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 13 publications
1
19
2
Order By: Relevance
“…On the other hand, the low temperatures exhibited lightly effect. These results are in concinnity with Brar et al (2005) and Sorokulova et al (2008) who found that the temperature above 50°C decreased the viability of spores and crystal protein. Ignoffo (1992) reported that the half-life of the toxin (Cry and Cyt) was less than 10 days at above 50°C and the half-life of dry spores exposed at 50°C was greater than 100 days.…”
Section: Effect Of Storage Under Accelerated Hot Storage and Shelf Lifesupporting
confidence: 87%
“…On the other hand, the low temperatures exhibited lightly effect. These results are in concinnity with Brar et al (2005) and Sorokulova et al (2008) who found that the temperature above 50°C decreased the viability of spores and crystal protein. Ignoffo (1992) reported that the half-life of the toxin (Cry and Cyt) was less than 10 days at above 50°C and the half-life of dry spores exposed at 50°C was greater than 100 days.…”
Section: Effect Of Storage Under Accelerated Hot Storage and Shelf Lifesupporting
confidence: 87%
“…The protectant effect of polymers was observed because the energy of activation increased when compared with the control (PBS), meaning that it takes more energy and time for cells to start degrading. The experimental values of the activation energy in our study (with a maximum value of 13.2 kcal/mol) were inferior to those described by other authors for Azotobacter (22.07 kcal/mol) and Bacillus spores (19.7 kcal/mol) when they were evaluating the effect of carrageenan, alginate and acacia gum over cell viability (Rojas-Tapias et al, 2015;Sorokulova et al 2008), but is necessary to highlight that, Azospirillum is much more sensitive to temperature than those microorganisms, and Bacillus spores are more resistant to any kind of stress. According to Dell et al (2007) and Huey and Kingsolver (2011), the use of the Arrhenius model is well accepted for biological processes, fitting in about 80 to 90% the behavior of thermal sensitivity among plants, microbes and animals.…”
Section: Screening Under Stress Conditionscontrasting
confidence: 96%
“…The data of the screening was analyzed using the ANOVA and HSD Tukey test. To calculate the rate of cell death, the Arrhenius equation was used as reported by Sorokulova et al (2008). Figures were made using Sigmaplot 13.0.…”
Section: Discussionmentioning
confidence: 99%
“…In current times, acacia gum is used extensively in food industry as an emulsifier, flavoring agent/adjuvant, formulation aid, stabilizer/thickener, humectant, surface-finishing agent; in pharmaceutical industry as a suspending agent, emulsifier, adhesive, and binder in tableting and in demulcent syrups; in cosmetics as stabilizer in lotions and protective creams, and an adhesive agent in blusher; foam stabilizer in liquid soaps; in lithography; in textile industry; in painting as dispersant in paints; and as dispersant in insecticidal/ acaricidal emulsions (Baldwin et al 1999;Joseleau and Ullmann 1990;Sanchez et al 2002). We discovered that one of the most important applications is the use of acacia gum in preserving microorganisms for extended periods of time without refrigeration (Krumnow et al 2009;Sorokulova et al 2008Sorokulova et al , 2012.…”
Section: Preservation With Biopolymersmentioning
confidence: 97%
“…The number of the spores released after storage was also increased when spores were treated with acacia gum prior to immobilization in tapioca and charcoal. Formulations of Bacillus spores with acacia gum and porous carriers (charcoal and tapioca) prolong the anticipated shelf life of spores even under ambient temperature and provide slow and steady bacterial release consistent with their high viability (Sorokulova et al 2008).…”
Section: Examples Of Preservation Of Microorganisms In Natural Biopolmentioning
confidence: 98%